#TITLE_ALTERNATIVE# - FIKRI HIDAYAT (NIM : 10207076); Pembimbing : Prof. Dr. Toto Winata, AULIA
VLS (Vapor-Liquid-Solid) mechanism is one of the most important mechanism in the fabrication of nanomaterial structure. Growth of catalyzed SiNW uses this mechanism. Growth of catalyst thin film is the initial step of this mechanism, which then followed by nanocluster formation by annealing process. This step then followed by the growth of SiNW on the catalyzed substrate. In this research SiNW is grown by HWC in plasma-VHF-PECVD (Hot Wire Cell in Plasma-Very High Frequency-Plasma Enhanced Chemical Vapor Deposition) method, which is a modification of the conventional PECVD. Thin Ni catalyst film has been grown on a microscope slide (glass) substrate. XRD (X-Ray Diffraction) spectroscopy characterization was used to identify its crystal structure and orientation. Annealing treatment was conducted on thin Ni film to obtain Ni nanocluster. Annealing was performed at constant temperature 600oC, with variation of time 4, 5, and 6 hours. XRD characterization results indicate the size of the crystals are 25,69 nm; 25,38 nm; and 16,88 nm respectively. XRD diffraction peak also indicates the crystal orientation of Ni in the [111] direction, and other peaks occured, which indicated NiO [111] and NiO[220]. The SiNW growth carried out on variation of rf power (radio frequency) 8, 10, and 20 watts. Morphological SEM (Scanning Electron Microscopy) results showed the average diameter of SiNW yield with the rf power 8, 10, and 20 watts are 1143,17 nm; 1490,27 nm; and 2605,26 nm respectively. Homogeneity in the diameter growth is still relatively low. Cross-section SEM results identified the yield vertical dimension, where the aspect ratio (length-width ratio) results of 8 watts varied (6,67; 6,86; and 23; 33) because of occurance of some structures which indicated wire in different locations. The 10 watts-aspect ratio is 3,125, while the aspect ratio of the 20 watts-yield is still relatively small. From EDS (Energy-Dispersive X-Ray) spectroscopy result indicated the chemical composition of oxygen impurities, which are still relatively high.